2015
DOI: 10.5455/gmj-30-170191
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture of health professionals

Abstract: Medical institutions should eliminate factors threatening patient safety to give the health service in quality. In this study main purpose is to determine the perception and attitude of health professionals on patient's safety. Material and Methods: A descriptive study was conducted at the university hospital through November 2010-February 2011. The population and sample of research were comprised of health professionals from all departments and response rate was 54% (n=261). Data collected with Hospital Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…The literature indicates that education is one of the recommendations/strategies for improving patient safety and increasing rates of reporting 22–25 . Bairami and Taleghani 18 (2016) stated that one of the main policies to prevent medical errors from being repeated is to inform healthcare personnel about what errors and near-miss errors mean.…”
Section: Intervention Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature indicates that education is one of the recommendations/strategies for improving patient safety and increasing rates of reporting 22–25 . Bairami and Taleghani 18 (2016) stated that one of the main policies to prevent medical errors from being repeated is to inform healthcare personnel about what errors and near-miss errors mean.…”
Section: Intervention Strategiesmentioning
confidence: 99%
“…The literature indicates that education is one of the recommendations/strategies for improving patient safety and increasing rates of reporting. [22][23][24][25] Bairami and Taleghani 18 (2016) stated that one of the main policies to prevent medical errors from being repeated is to inform healthcare personnel about what errors and near-miss errors mean. A study by Jansma et al 9 (2011) reported that patient safety education had positive effects on the participants' knowledge, skills, and attitudes in the short and long term, and affected their reporting behavior.…”
Section: Intervention Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…İç girişimciliğin boyutu olan "yeni girişimlerin başlatılması" sırasında "yenilikçilik", "proaktiflik", "risk alma" ve "özerklik" boyutları sürekli gündemde olmak zorundadır (5). Büyük ve küçük işletmelerde de yeni iş geliştirmeye yönelik girişimcilik, bağımsız birim veya işletme biçiminde oluşturulmaktadır (19 (22). Son yıllarda hasta güvenliği açık bir şekilde uluslararası bir sorun olarak görülmektedir.…”
Section: İç Girişimcilik Boyutlarıunclassified
“…Hasta güvenliği, tüm sağlık sistemlerinin ve kalite güvence çalışmaların önemli bir bileşeni olan bir konudur. Kaliteli sağlık hizmeti sunabilmek için hasta güvenliğini tehdit eden faktörlerin azaltılması ve ortadan kaldırılması gerekmektedir (22). Son yıllarda hasta güvenliği açık bir şekilde uluslararası bir sorun olarak görülmektedir.…”
Section: Hasta Güvenli̇ği̇unclassified